2013
DOI: 10.1002/ejlt.201200375
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and sensory assessment of deep‐frying oil alternatives for the processing of French fries

Abstract: The aim of the study was to evaluate volatile compounds as marker compounds for the edible oil deterioration during the production of deep-fried French fries. Additionally the sensory characteristics (taste and smell) were assessed and results were compared with the results of the volatile compound analysis. A 32-h deep-frying experiment was performed and different frying oils, namely sunflower oil (SF), high-oleic sunflower oil (HOSF), rapeseed oil (RO), high-oleic rapeseed oil (HORO), and palm olein, were su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
30
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 36 publications
(54 reference statements)
7
30
0
Order By: Relevance
“…Conversely, in CO, RO, and LO, which contained appreciable amounts of linoleic fatty acid chains, HNE content reached approximately 3.70, 1.70, and 1.91 μg g À1 oil, respectively; HNE was abundant in oils rich in ω-6 PUFA. [29,30] Despite RO (18.34%) possessing a higher ω-6 level than LO (14.45%), HNE content in RO was lower than that in LO, mainly due to the high ω-3 PUFA content in LO, which promoted the peroxidation of ω-6 PUFA and the subsequent formation of HNE. [28] Our results showed that the formation of MDA, HHE, and HNE was simultaneous and somewhat competitive.…”
Section: Contents Of Mda Hhe and Hne In Different Tested Oils Durinmentioning
confidence: 99%
“…Conversely, in CO, RO, and LO, which contained appreciable amounts of linoleic fatty acid chains, HNE content reached approximately 3.70, 1.70, and 1.91 μg g À1 oil, respectively; HNE was abundant in oils rich in ω-6 PUFA. [29,30] Despite RO (18.34%) possessing a higher ω-6 level than LO (14.45%), HNE content in RO was lower than that in LO, mainly due to the high ω-3 PUFA content in LO, which promoted the peroxidation of ω-6 PUFA and the subsequent formation of HNE. [28] Our results showed that the formation of MDA, HHE, and HNE was simultaneous and somewhat competitive.…”
Section: Contents Of Mda Hhe and Hne In Different Tested Oils Durinmentioning
confidence: 99%
“…polymerised and oxidised TAG, DAG and FFAdeveloped during excessive heat treatment 25 . Oils containing high level of polar compounds are potentially toxic and can be easily absorbed by human body 27 . As such, many countries have opted to establish regulatory limits for polar compounds varying from 25 and 30 3,22 .…”
Section: Polar Compoundsmentioning
confidence: 99%
“…Consequently, these changes reduce consumer acceptance to the final product. In this regard, wide range of antioxidants, either synthetic or natural, are added to fats, oils, and foods containing fats to inhibit the development of off-flavors arising from the oxidation of unsaturated fatty acids [2] [9][10] [11] [12] [13][14] [5].…”
Section: Issn: 2320-5407mentioning
confidence: 99%